Human ornithine-delta-aminotransferase. cDNA cloning and analysis of the structural gene. - Grant A. Mitchell; James E. Looney; Lawrence C. Brody; Gary Steel; Maureen K. Suchanek; John F. Engelhardt; H.F. Willard; David Valle (1988)
Abstract Ornithine-delta-aminotransferase (OAT) is a nuclear-encoded, mitochondrial matrix enzyme which, in rat, is expressed as basal levels in most tissues but is induced in liver by high dietary protein and in kidney by estrogen and thyroxine administration. In man, the hereditary deficiency of OAT results in ornithine accumulation and the blinding disease gyrate atrophy of the choroid and retina. We cloned near full length rat and human liver OAT cDNAs and demonstrated OAT expression in a variety of tissues from each species. We mapped the human OAT structural gene to chromosome 10, cloned 40 kilobase pairs of genomic DNA containing the complete OAT structural gene, and determined its organization. It is 21 kilobase pairs in length, and contains 11 exons. Exon 2 has been absent from all cDNAs studied and was detected by homology to X-linked processed OAT pseudogenes. The 5'-flanking region of the OAT gene has features of housekeeping genes (GC enrichment and three Sp1 binding consensus sequences) and tissue-specific, inducible genes (TATA box-like element and two CCAAT boxes). A 22-base pair region of partial dyad symmetry containing homology to estrogen responsive elements overlaps the OAT transcription site. Another 5' sequence, GTATCCTGCCCTC, is homologous to sequences in the promoter regions of the genes of three urea cycle enzymes.